2015
DOI: 10.1037/dev0000029
|View full text |Cite
|
Sign up to set email alerts
|

Early social deprivation and the social buffering of cortisol stress responses in late childhood: An experimental study.

Abstract: The goal of the present study was to investigate the role of early social deprivation in shaping the effectiveness of parent support to alleviate hypothalamic-pituitary-adrenal (HPA) axis stress responses of children (ages 8.9–11, M = 9.83 years, SD = .55). The sample was equally divided between children who had been adopted internationally from orphanage care by age 5 (N = 40) and an age- and gender-matched group of non-adopted children (N = 40). On average, internationally adopted children were invited to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 63 publications
(112 reference statements)
4
68
0
1
Order By: Relevance
“…Unlike the relatively low basal and stress-induced cortisol responses during childhood, basal cortisol increases from childhood to adolescence and is positively associated with pubertal development (Gunnar et al, 2009b; Gunnar and Vazquez, 2006; Hostinar et al, 2015; Legro, 2003; Netherton et al, 2004; Stroud et al, 2009; Törnhage, 2002). In a sample of almost 400 youth aged 7–15 years, for example, diurnal cortisol was found to positively correlate with pubertal stage (Kiess et al, 1995).…”
Section: 1 Theoretical and Empirical Support For Examining The Rolementioning
confidence: 95%
See 2 more Smart Citations
“…Unlike the relatively low basal and stress-induced cortisol responses during childhood, basal cortisol increases from childhood to adolescence and is positively associated with pubertal development (Gunnar et al, 2009b; Gunnar and Vazquez, 2006; Hostinar et al, 2015; Legro, 2003; Netherton et al, 2004; Stroud et al, 2009; Törnhage, 2002). In a sample of almost 400 youth aged 7–15 years, for example, diurnal cortisol was found to positively correlate with pubertal stage (Kiess et al, 1995).…”
Section: 1 Theoretical and Empirical Support For Examining The Rolementioning
confidence: 95%
“…In one study, 7–12 year old female youth exhibited an attenuated cortisol response and quicker recovery from social evaluation when reunited with their mothers (Seltzer et al, 2010). Similarly, parental support blunted cortisol responses to social evaluation among 9–10 year old children (Hostinar et al, 2015). …”
Section: 1 Theoretical and Empirical Support For Examining The Rolementioning
confidence: 99%
See 1 more Smart Citation
“…Statistically extreme values (> 3 SD from the mean) which were not explained by illness or medication use were winsorized. Variables were then log transformed using a log10 transformation to meet the assumptions of normality (Brummelte et al, 2011; Grunau et al, 2007; Hostinar, Johnson, & Gunnar, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Importantly, positive attention bias in foster care youth predicted lower externalizing symptoms at age 8 and lower internalizing problems at age 12, suggesting that positivity-bias following early foster-care placement is associated with improved socioemotional functioning in the long-term (Troller-Renfree et al, 2015; Troller-renfree et al, 2016). However, a recent study of internationally adopted PI children and adolescents found that parental presence during a social stress task had no greater regulatory effect on cortisol reactivity relative to stranger presence, suggesting that social buffering mechanisms may exert differential effects on stress-related neurobiology depending on prior social experiences (Hostinar, Johnson, & Gunnar, 2015). Moreover, animal models have shown that social buffering effects are diminished following atypical caregiving experiences (i.e.…”
Section: Protective Factors and Neuro-affective Development Followimentioning
confidence: 99%